2013
DOI: 10.1177/0022034513505768
|View full text |Cite
|
Sign up to set email alerts
|

The Circadian Clock in Oral Health and Diseases

Abstract: Most physiological processes in mammals display circadian rhythms that are driven by the endogenous circadian clock. This clock is comprised of a central component located in the hypothalamic suprachiasmatic nucleus and subordinate clocks in peripheral tissues. Circadian rhythms sustain 24-hour oscillations of a large number of master genes controlling the correct timing and synchronization of diverse physiological and metabolic processes within our bodies. This complex regulatory network provides an important… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
68
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(69 citation statements)
references
References 64 publications
1
68
0
Order By: Relevance
“…The finding of "endoplasmic reticulum membrane" as the top gene set associated with severe periodontitis parallels recent emerging data on the importance of endoplasmic reticulum stress in periodontitis (Domon et al, 2009;Lee et al, 2012). "Circadian clock rhythm" was the top enriched pathway for high colonization with red complex pathogens and has gained recent attention in oral health research (Papagerakis et al, 2014). Interestingly, Keller et al (2009) recently reported that on the molecular level, >8% of the macrophage transcriptome oscillates in a circadian fashion, including many important regulators for pathogen recognition and cytokine secretion.…”
Section: Discussionmentioning
confidence: 58%
“…The finding of "endoplasmic reticulum membrane" as the top gene set associated with severe periodontitis parallels recent emerging data on the importance of endoplasmic reticulum stress in periodontitis (Domon et al, 2009;Lee et al, 2012). "Circadian clock rhythm" was the top enriched pathway for high colonization with red complex pathogens and has gained recent attention in oral health research (Papagerakis et al, 2014). Interestingly, Keller et al (2009) recently reported that on the molecular level, >8% of the macrophage transcriptome oscillates in a circadian fashion, including many important regulators for pathogen recognition and cytokine secretion.…”
Section: Discussionmentioning
confidence: 58%
“…It is anticipated that circadian clock research will contribute to broader understanding of how mineralized tissues are formed. A system’s biology approach having as “skeleton” the circadian system may help us understand how mineralized tissues are developed in synchrony [17]. New inputs such as mastication or bone load could be established in the circadian system equation increasing our understanding of this complex communication between the brain and the peripheral organs.…”
Section: Discussionmentioning
confidence: 99%
“…In oral health, the possibilities of clock genes involvement into patho-physiology of oral and craniofacial tissues remain largely unexplored [17]. This review summarizes the potential roles of clock genes in dental tissues formation with a special focus on enamel development.…”
Section: Introduction To the Circadian Clockmentioning
confidence: 99%
“…All circadian rhythms are directed by the biological clock located in the hypothalamus, and interfere with the salivary flow, the oral epithelium, and inflammatory response, even in the IL-6 route 122 . BMS patients have low serum IL-6 levels, which play a neuroprotective role in the trigeminal nociceptive pathway through the underlying mechanisms thereof remain to be ellucidated 117 .…”
Section: Chronobiologymentioning
confidence: 99%